TEACHERS’ PERSPECTIVES ON PROJECT-BASED LEARNING INTEGRATED WITH ESD-STEM IN TEACHING PHOTOSYNTHESIS TO FOSTER CRITICAL THINKING - Lusi Ayu Gustari; Ghullam Hamdu (RADJA PUBLIKA, 2026)
This study was motivated by the need for science education that can develop critical thinking skills in elementary school students through a contextual and sustainable approach. The integration of Project-Based Learning (PjBL), Education for Sustainable Development (ESD), and STEM is seen as a relevant innovative strategy, but its implementation in the field has not been fully structured. This study aims to analyze teachers' perspectives on the application of ESD-STEM integrated PjBL in photosynthesis learning and to examine its implications for the development of students' critical thinking skills. The research used a qualitative approach with an instrumental case study design conducted in three public elementary schools in Bungursari District, Tasikmalaya City. Data were obtained through in-depth interviews, learning observations, and documentation studies, then analyzed through a process of reduction, categorization, and thematic interpretation. The results showed that teachers had implemented project-based learning that encouraged active student involvement and fostered problem identification, cause-and-effect analysis, and data-based conclusion drawing skills, although the integration of ESD and STEM was still implicit and not yet fully systematic. This study concludes that the development of structured and reflective PjBL-ESD-STEM integrated teaching modules is necessary to optimize the development of students' critical thinking in sustainability-based science learning.